An investigation of how visual arts can be used to teach mathematical concepts of space and shape in Grade R - Schäfer, Jean Stewart (Rhodes University, Faculty of Education, Department of Education, 2011)
The impetus for this study came from the findings of an evaluation of a Maths and Science through Arts and Culture (MStAC) Curriculum Intervention undertaken with Grade R teachers registered for a BEd(in-service) qualification at Rhodes University, South Africa. The intervention aimed to enrich Grade R teachers' teaching of mathematics. Post-intervention classroom observations showed that, in spite of the intervention, teachers' classroom practices did not change, and they were not using visual arts to teach mathematical concepts. This, together with the lack of research in the field of mathematics in early childhood, particularly in South Africa, motivated this research, a case study, which investigates how visual arts can be used to teach space and shape conceptualization in Grade R. I designed a research intervention underpinned by a constructivist model of teacher professional development located in reflective practice (Borko & Putman, 1995; Zeichner & Liston, 1996; Wilmot, 2005). Guided by Stacey's (2009) notion of an emergent curriculum, I designed a three phase research intervention which involved selected Grade R teachers undertaking classroom-based research. Phase I built awareness around the notion of creativity; Phase II focused on making meaning of children's behaviour and interests; and Phase III applied the knowledge and ideas from the Phases I and II to the teaching of space and shape. As an interpretive research study, it closely examines the participating teachers' perceptions, experiences and reflections which were articulated in reflective reports and assignments. Following action research processes, the participant teachers engaged in the process of an emergent curriculum. They observed the behaviour interests of Grade R children, interpreted and made meaning of the evident behaviours, made decisions regarding extension activities, and planned accordingly. The findings of the study illuminate a model of teacher professional development that can support and enhance teachers' practice. Understanding the notion of creativity and the ability to create a classroom conducive to creativity, are necessary components for teaching space and shape through visual arts activities. An emergent curriculum approach is proposed as an appropriate pedagogy for teaching children about space and shape through visual arts activities.
Keywords: Rhodes University. Deptartment of Education; Mathematics -- Study and teaching (Elementary) -- South Africa--Grahamstown; Mathematics teachers -- Training of -- South Africa -- Grahamstown; Early childhood education -- South Africa -- Grahamstown; Kindergarten -- Activity programs -- South Africa -- Grahamstown; Creative activities and seat work -- South Africa -- Grahamstown